An Overview on Bioenhancers - Asif, Mohammad; Kala, Chandra; Ahmad, Tabassum Wasim (Challenges and Advances in Pharmaceutical Research Vol. 10, 2022)
A bioenhancer is an agent that increases the bioavailability and bioefficacy of a medicine when added to it but has no pharmacological effect of its own at the dose employed. Bioenhancers should be inert, non-toxic, compatible with active pharmaceutical ingredients, cost-effective, stable, easy to formulate into various forms, and readily available. Bioenhancers act by several mechanisms, such as alteration of fluidity of the plasma membrane, hence promoting passive transcellular drug penetration; modulation of tight junctions to allow for increased paracellular diffusion; modulation of active efflux transporters such as P-gp-related efflux inhibition; inhibition of CYP enzymes in the intestinal epithelium and liver, exerting cholagogue/choleretic effect; and exerting thermogenesis. Popular herbal bioenhancers include piperine, naringin, quercitin, curcumin, genistein, sinomenine, and capsaicin. The vast research to elaborate on the promising effects of using bioenhancers has shown promising outcomes in both in-vitro and in-vivo studies. However, it is clear that there is a long way to go before we can fully commercialise the use of bioenhancers in combination with medicine to optimise the advantages of treatments. This review shed light on various aspects of bioenhancers.